Pemanfaatan Media Kahoot untuk Evaluasi Pembelajaran Fiqh pada Siswa Kelas X di MAN 2 Karawang - Putri, Rika Amalia; Hermawan, Iwan; Farida, Nur Aini; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2024)
There are several things that encourage the writer to be interested in examining the problems in this research, namely: The implementation of evaluations in schools is still very monotonous. At the Madrasah Aliyah Negeri 2 Karawang school, the evaluation still uses ordinary written tests, so that it makes students easily bored in carrying out learning evaluations, especially in evaluating Fiqh learning. This is evidenced by the knowledge of students who do not understand material about buying and selling, khiyar, greetings and hajr. In overcoming problems in the process of implementing learning evaluation, it is necessary to have a learning media, in increasing student learning motivation there are several media that can be used by students, one of which is using kahoot media. This research was conducted at Madrasah Aliyah Negeri Karawang which is located at Jl.Syech Quro Km.5 No.1 Plawad, Palawad, Kec.Karawang Timur, Kab.Karawang Prov.Jawa Barat. for this research was carried out from February 20 to February 24, 2023. Researchers focused more on qualitative data in conducting this research. With data collection instruments using interviews, observation, documentation